Perancangan Alat Sistem Keamanan Kendaraan Berbasis SMS dan GPS - Elvin Syahrin (CV. ITTC INDONESIA, 2024)
Motor vehicle theft is currently rampant, making it difficult for owners to recover their lost vehicles and forcing them to be constantly vigilant. Tracking the position of the vehicle during theft is a challenge for vehicle owners. A security system based on SMS and GPS for vehicles allows owners to track the location of their vehicles when theft occurs. They can also control the vehicle's power via SMS. The remote control system utilizes an SMS modem, while location reading utilizes a GPS module. To determine the vehicle's location, simply send an SMS